IDENTIFIKASI FAKTOR PENENTU MOBILITAS DI KECAMATAN SUKARAJA - Alnur Fitria Ningsih; Hutapia Hutapia (Convergence: The Journal of Economic Development, 2019)
This study aimed to analyze the charasteristics factors which are able to influence the workers decision to commit commuting migration in Sukaraja subdistrict of Seluma regency. This research is descriptive  research that will analyze the effect charasteristics  of  wage, age , level of education, marriage, sex and land to the workers decision to commit commuting migration in Sukaraja subdistrict of Seluma regency. The research was conducted  by an experimental apptoach using primary data. Samples were taken as 100 respondents in proportional random sampling with random  sampling method. Analysis of the data used descriptive analysis . The results showed  difference in  charasteristics  of  wage, age , level of education, marriage, sex and land to influence the workers decision to commit commuting migration in Sukaraja subdistrict of Seluma regency.Keywords: commuting migration, wage, age , level of education, marriage, sex and land